1,1-Diphenyl-4-(thiophen-2-yl)but-3-yn-1-ol - Umaña, Christian A. (2018)
The asymmetric unit of the title homopropargyl alcohol, C20H16OS, contains two independent molecules comprising a hydroxy group, a 3-(2-thiophenyl)- propargylic moiety and two aromatic rings linked to a central carbon atom. The two unique molecules are linked into a dimer by an O—HO hydrogen bond. In one molecule, the thiophene ring is disordered over two orientations rotated by 180 with a refined occupancy ratio of 0.575 (4):0.425 (4). The crystal structure is stabilized by O—H and C—H hydrogen-bond interactions. The crystal studied was a two-component non-merohedral twin, the refined ratio of the twin components being 0.575 (4):0.425 (4).